2022
DOI: 10.1002/ps.6793
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification, characterization and functional analysis of the chitianse and chitinase‐like gene family in Diaphorina citri

Abstract: BACKGROUND Insect chitinases play vital roles in postembryonic development, especially during the molting process, and are potential targets for the RNA interference (RNAi)‐based insecticidal strategy. Systematic functional analyses of chitinase genes have already been conducted on numerous insect pests, but similar analyses have not been carried out on Diaphorina citri. RESULTS Eleven chitinase/chitinase‐like genes and one endo‐β‐N‐acetylglucosaminidase (ENGase) gene were identified in the Diaphorina citri ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Knockdown of the other chitinase genes will probably have only subtle effects, possibly because of redundancy, and understanding the function of these genes will require more extensive analysis. While this manuscript was under review, Wu et al [33] published an independent characterization of D. citri chitinase genes with very similar results. They performed RNAi with each of the genes and, as we predicted, found that only DcCht5, DcCht7, DcCht10-1 and DcCht10-2 affected molting.…”
Section: Expression Of Chitinase Genes In D Citrimentioning
confidence: 70%
See 1 more Smart Citation
“…Knockdown of the other chitinase genes will probably have only subtle effects, possibly because of redundancy, and understanding the function of these genes will require more extensive analysis. While this manuscript was under review, Wu et al [33] published an independent characterization of D. citri chitinase genes with very similar results. They performed RNAi with each of the genes and, as we predicted, found that only DcCht5, DcCht7, DcCht10-1 and DcCht10-2 affected molting.…”
Section: Expression Of Chitinase Genes In D Citrimentioning
confidence: 70%
“…While this manuscript was under review, Wu et al. [ 33 ] published an independent characterization of D. citri chitinase genes with very similar results. They performed RNAi with each of the genes and, as we predicted, found that only DcCht5 , DcCht7 , DcCht10-1 and DcCht10-2 affected molting.…”
Section: Data Validation and Quality Controlmentioning
confidence: 77%
“…An analysis of chitinase counts in various insects revealed an interesting finding (Table S4). Hemimetabolous insects, such as Diaphorina citri , 20 N. lugens , 24 Bemisia tabaci , 14 and Acyrthosiphon pisum 45 possess fewer chitinase‐like genes. This can be attributed to their reduced need for enzymes and energy during integument reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Insect chitinases, specifically those belonging to groups I (Cht5), II (Cht10), and III (Cht7), play crucial roles in the degradation of old exoskeletons 19,20,22 . Previous studies have demonstrated the involvement of Cht5 in the pupal‐to‐adult eclosion process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation